2009
DOI: 10.1007/s00198-009-0931-0
|View full text |Cite
|
Sign up to set email alerts
|

Wnt pathway genes in osteoporosis and osteoarthritis: differential expression and genetic association study

Abstract: Summary In comparison with hip fractures, increased expression of genes in the Wnt pathway and increased Wnt activity were found in bone samples and osteoblast cultures from patients with osteoarthritis, suggesting the involvement of this pathway in subchondral bone changes. No consistent differences were found in the genetic association study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 49 publications
3
48
1
Order By: Relevance
“…In adult life, Wnt signaling continues to play an important role in joint homeostasis. Excessive activation of this pathway is involved in regulating cartilage breakdown and bony sclerosis in osteoarthritis [57], and single-nucleotide polymorphisms (SNPs) of Wnt pathway proteins are associated with increased susceptibility to osteoarthritis [5861]. Antagonists of the Wnt pathway are currently in clinical development for treatment of the sclerotic bony lesions of multiple myeloma [62] and osteoporosis [63], though their efficacy has not yet been tested in osteoarthritis.…”
Section: Bone Morphogenetic Proteins and The Wingless Pathway: Molecumentioning
confidence: 99%
“…In adult life, Wnt signaling continues to play an important role in joint homeostasis. Excessive activation of this pathway is involved in regulating cartilage breakdown and bony sclerosis in osteoarthritis [57], and single-nucleotide polymorphisms (SNPs) of Wnt pathway proteins are associated with increased susceptibility to osteoarthritis [5861]. Antagonists of the Wnt pathway are currently in clinical development for treatment of the sclerotic bony lesions of multiple myeloma [62] and osteoporosis [63], though their efficacy has not yet been tested in osteoarthritis.…”
Section: Bone Morphogenetic Proteins and The Wingless Pathway: Molecumentioning
confidence: 99%
“…CELL CULTURE hOB cells were obtained from bone specimens extracted from knee samples otherwise discarded at the time of orthopaedic surgery in postmenopausal women, as described previously [Garcia-Moreno et al, 2002;Velasco et al, 2009] [Brandstrom et al, 1998;Hofbauer et al, 1998;Fuller et al, 2000]. For each treatment, concentration, and time, three replicate plates were used.…”
Section: Subjectsmentioning
confidence: 99%
“…On the other hand, Wnt activity has been reported to influence cartilage 346 metabolism and may be involved in the pathogenesis of osteoarthritis 347 (Corr, 2008;Diarra et al, 2007;Lodewyckx and Lories, 2009;Luyten 348 et al, 2009 showed higher Wnt activity in osteoblasts from patients with osteoar-372 thritis than in those obtained from fracture cases (Velasco et al, 2010).…”
mentioning
confidence: 99%